Two-dimensional amorphous copper-based MOF material and preparation method and application thereof

By reacting organic ligands, copper salts and organic solvents in a closed environment in a one-step manner, the two-dimensional amorphous copper-based MOF materials are directly synthesized, solving the problem of complex steps and low efficiency in the preparation of amorphous MOF materials in the prior art, and a simple and efficient preparation process is achieved.

CN119708529AActive Publication Date: 2025-03-28UNIV OF SCI & TECH OF CHINA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510025271.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-03-28
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The prior art has complex steps and low efficiency in preparing amorphous MOF materials, which requires multiple processing and special equipment operations, making it difficult to achieve large-scale production.

Method used

The mixed solution of organic ligand, copper salt and organic solvent is reacted in a closed environment by a one-step method to directly synthesize two-dimensional amorphous copper-based MOF material, avoiding the secondary treatment step.

Benefits of technology

It realizes the preparation of a simple and efficient two-dimensional amorphous copper-based MOF material, with simple operation, easy control of conditions, wide applicability, and high yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a two-dimensional amorphous copper-based MOF material and a preparation method and application thereof. The preparation method comprises the following steps: reacting a mixed solution of an organic ligand, a copper salt and an organic solvent in a closed environment to obtain the two-dimensional amorphous copper-based MOF material. According to the preparation method provided by the invention, the two-dimensional amorphous MOF material can be directly synthesized in one step, secondary treatment is not needed, and the preparation method is different from the commonly used preparation methods for inducing crystal collapse, such as fluid static pressure, heating, mechanical stress, radiation, discharge and the like. Meanwhile, a catalyst prepared from the two-dimensional amorphous MOF material is used for electrocatalytic CO2 reduction, the selectivity of C2 + products including ethylene and ethanol can be effectively improved, and excellent catalytic activity is shown. In addition, the preparation process is simple to operate, conditions are easy to control, the applicability is wide, and the yield is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal organic complexes, and in particular relates to a two-dimensional amorphous copper-based MOF material and a preparation method and application thereof. Background Art

[0002] In recent years, with the continuous progress of industrial civilization, the massive consumption of fossil fuels has not only triggered an energy crisis, but also led to a large amount of carbon dioxide emissions, exacerbating environmental problems such as the greenhouse effect and global warming. At present, since it is impossible to find materials that can completely replace fossil fuels in the short term, it is necessary to develop efficient, stable and feasible carbon dioxide conversion technologies to reduce carbon dioxide emissions. Studies have reported that copper-based catalysts can electrocatalytically reduce CO2 into a variety of chemical products with a wide range of uses under mild conditions. Among them, the multi-carbon products such as ethylene and ethanol obtained by reduction have high economic value and energy density, but there are still problems such as wide distribution of products and C 2+ The product selectivity is not high and other difficulties and challenges. Therefore, optimizing copper-based catalysts is particularly critical to improving product selectivity and product distribution.

[0003] Metal-organic frameworks (MOF) are materials with periodic porous network structures formed by self-assembly between metal organic ligands and metal ions through metal-ligand complexation. Due to their adjustable pore structure, large specific surface area, stable chemical properties and other characteristics, they are widely used in catalysis, pharmaceutical materials, energy storage and other fields. Amorphous MOF materials have both the common characteristics of crystalline MOF materials, including excellent thermal stability, high surface area, high porosity and adjustable pore structure, and the unique advantages of amorphous materials, such as isotropy, no grain boundary structure, abundant defects and active sites. Therefore, compared with crystalline MOF materials, amorphous MOF materials show better performance in the field of catalysis.

[0004] At present, most amorphous MOF materials are prepared by applying stress to the crystal framework. For example, physical treatment methods such as static pressure and fluid static pressure, heating, mechanical stress (ball milling, grinding, etc.), radiation and discharge have been applied to crystalline MOF materials to induce the collapse of their crystal structure; in addition, chemical treatment of amorphization can also cause crystal failure. However, the above preparation methods are complicated. Generally, crystalline MOF materials need to be prepared by solvothermal method, and then the crystalline MOF is subjected to secondary treatment to make it amorphous. At the same time, the secondary treatment process is difficult and most of them require special instruments and equipment to operate. For example, hydrostatic pressure treatment requires placing crystalline MOF powder in a diamond anvil cell (DAC) and compressing the sample with a non-pressure fluid or methanol-ethanol-water (MEW) isopropanol or perfluorotripentylamine (FC-70); while amorphization treatment methods such as ball milling and grinding provide less mechanical stress, which is difficult to destroy the crystal structure, takes up to several weeks, and has low efficiency. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a two-dimensional amorphous copper-based MOF material and a preparation method and application thereof. The preparation method can directly synthesize the amorphous MOF material in one step without secondary treatment, which is simple, convenient and efficient.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a two-dimensional amorphous copper-based MOF material, comprising the following steps:

[0008] A mixed solution of organic ligand, copper salt and organic solvent is reacted in a closed environment to obtain a two-dimensional amorphous copper-based MOF material;

[0009] Preferably, the organic ligand is selected from any one or more of 2-hydroxyterephthalic acid, 2,3-dihydroxybenzoic acid, 2,3-dihydroxyterephthalic acid, 2,5-dihydroxyterephthalic acid, 2,5-dihydroxybenzoic acid, 2,6-dihydroxybenzoic acid, 4-hydroxybenzoic acid or p-hydroxybibenzoic acid.

[0010] Preferably, the organic solvent is a mixed solvent of N,N-dimethylformamide and acetonitrile, and the volume ratio of N,N-dimethylformamide to acetonitrile is 5:1 to 1:11.

[0011] Preferably, the copper salt is selected from any one or more of Cu(NO3)2, Cu(NO3)2•3H2O, CuSO4, CuSO4•5H2O, CuCl2, CuCl2•2H2O, CuCrO4•2H2O or CuCr2O7•2H2O.

[0012] Preferably, the molar ratio of copper in the copper salt to the organic ligand is 4:1 to 1:13.

[0013] Preferably, the molar ratio of copper in the copper salt to the organic ligand is 4:1 to 1:8.

[0014] Preferably, the volume ratio of N,N-dimethylformamide to acetonitrile is 3:1 to 1:6.

[0015] Preferably, the mixed solution of the organic ligand, copper salt and organic solvent is obtained by dissolving the organic ligand and copper salt in the organic solvent.

[0016] Preferably, the dissolving is carried out at a rotation speed of 50 to 1400 rpm.

[0017] Preferably, the pH value of the mixed solution is 1-6.7.

[0018] Preferably, the reaction is carried out at 2-20 °C min -1 The temperature is raised to 50~220℃ at a rate of 1.

[0019] Preferably, the reaction is kept at 50-220° C. for 6-72 h.

[0020] Preferably, the reaction further includes washing and drying steps.

[0021] In a second aspect, the present invention also provides a two-dimensional amorphous copper-based MOF material prepared by the above preparation method, wherein the two-dimensional amorphous copper-based MOF material is a two-dimensional nanosheet structure.

[0022] In a third aspect, the present invention also provides an application of the above-mentioned two-dimensional amorphous copper-based MOF material in electrocatalytic CO2 reduction.

[0023] Preferably, in the electrocatalytic CO2 reduction, the working electrode comprises the above-mentioned two-dimensional amorphous copper-based MOF material.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The present invention provides a one-step method for preparing a two-dimensional amorphous copper-based MOF material, which uses acetonitrile and the carboxyl and hydroxyl groups of organic ligands to react with metal Cu 2+ The competitive coordination of ions causes the metal organic framework to twist and extend, thereby reacting under high pressure and high temperature conditions, and directly self-assembling to form a non-periodic metal organic framework in one step. It can be seen that the preparation method provided by the present invention can directly synthesize two-dimensional amorphous MOF materials in one step without secondary treatment. Compared with the currently commonly used preparation methods of inducing crystal collapse by hydrostatic pressure, heating, mechanical stress, radiation and discharge, the steps are simpler and easier to implement, which is conducive to promoting large-scale production.

[0026] At the same time, the present invention applies the two-dimensional amorphous copper-based MOF material prepared according to the method to a flow cell system for electrocatalytic CO2 reduction. The test results show that compared with the existing MOF materials, the non-periodic structure of the two-dimensional amorphous copper-based MOF material has a relatively excellent catalytic activity. In particular, the catalyst can effectively increase the C2+, including ethylene, ethanol and acetic acid. 2+ The selectivity of the product, C 2+ The Faraday efficiency of the product is as high as 68.7%, which has certain advantages in MOF materials. In addition, the preparation process is simple to operate, the conditions are easy to control, the applicability is wide, and the yield is high. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 XRD diagrams of copper-based MOF materials obtained in Example 1 and Comparative Examples 1-2; wherein a corresponds to Example 1, b corresponds to Comparative Example 1, and c corresponds to Comparative Example 2;

[0028] Figure 2 This is a SEM image of the two-dimensional amorphous copper-based MOF material obtained in Example 1;

[0029] Figure 3 TEM image of the two-dimensional amorphous copper-based MOF material obtained in Example 1;

[0030] Figure 4 This is a Faraday efficiency diagram of the electrocatalytic CO2 reduction of various products using the working electrode prepared using the two-dimensional amorphous Cu-based MOF material in Example 1 as a catalyst. DETAILED DESCRIPTION

[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] In view of the problems of complicated steps and low efficiency in the preparation of amorphous MOF materials in the prior art, the present invention provides a method for preparing a two-dimensional amorphous copper-based MOF material, comprising the following steps:

[0033] A mixed solution of organic ligand, copper salt and organic solvent is reacted in a closed environment to obtain a two-dimensional amorphous copper-based MOF material.

[0034] In the present invention, the mixed solution of the organic ligand, copper salt and organic solvent is obtained by dissolving the organic ligand and copper salt in an organic solvent. The mixed solution is a clear solution. The dissolution is preferably carried out under stirring, and the stirring speed is 50~1400 rpm, preferably 300~1000 rpm, and more preferably 600~800 rpm; the mixed solution is a strongly acidic solution, and its pH value is 1~6.7, preferably 1~4.7. In some embodiments of the present invention, after obtaining the mixed solution, it is necessary to repeatedly measure the pH value of the reaction solution to ensure that the test error is ≤0.2, and then the mixed solution is subjected to subsequent reactions.

[0035] In the present invention, the copper salt is a salt compound formed by +2-valent copper ions and other non-metallic elements (such as oxygen, sulfur, chlorine, etc.). Specifically, in some embodiments of the present invention, the copper salt is selected from any one of Cu(NO3)2, Cu(NO3)2•3H2O, CuSO4, CuSO4•5H2O, CuCl2, CuCl2•2H2O, CuCrO4•2H2O or CuCr2O7•2H2O or a mixture of any proportions thereof. The present invention has no particular restrictions on the source of the copper salt, and it can be a general commercial product.

[0036] In the present invention, the organic ligand is an organic compound that can form a coordination bond with the central atom of a metallic copper ion or a copper compound and has an adjustable bond length, and can be specifically selected from any one or more of 2-hydroxyterephthalic acid, 2,3-dihydroxybenzoic acid, 2,3-dihydroxyterephthalic acid, 2,5-dihydroxyterephthalic acid, 2,5-dihydroxybenzoic acid, 2,6-dihydroxybenzoic acid, 4-hydroxybenzoic acid or p-hydroxybibenzoic acid, preferably 2,5-dihydroxyterephthalic acid (abbreviated as: DHTA).

[0037] In some embodiments of the present invention, the molar ratio of Cu in the copper salt to the organic ligand is 4:1 to 1:13, preferably 4:1 to 1:8, and more preferably 2:1 to 1:5.6.

[0038] In the present invention, the organic solvent is a mixed solvent of N,N-dimethylformamide and acetonitrile. The ratio of the two has a great influence on the structure of the final product. If the ratio of acetonitrile is too low, the cyano group provided in the coordination complex process will be insufficient, and it will not be able to fully compete with the carboxyl and hydroxyl groups provided by DHTA, which will lead to the partial Cu 2+It cannot be complexed with the corresponding functional group and is directly reduced to elemental Cu. On the contrary, too high a proportion of acetonitrile will reduce the solubility of DHTA and copper salt in the solvent, thereby causing the reaction solution to react insufficiently during the hydrothermal process. Therefore, in some embodiments of the present invention, the volume ratio of N,N-dimethylformamide to acetonitrile is 5:1 to 1:11, preferably 3:1 to 1:6, and more preferably 3:2 to 1:4.

[0039] In some embodiments of the present invention, the copper salt and the organic ligand are preferably dispersed and dissolved in an organic solvent respectively to obtain a copper salt solution and an organic ligand solution, and then the organic ligand solution is slowly poured into the copper salt solution and mixed thoroughly to obtain a mixed solution. The composition and dosage of the copper salt and the organic ligand, as well as the dissolution parameters, are all referred to the above-mentioned related content and will not be repeated here.

[0040] After the mixed solution is obtained, according to the present invention, the mixed solution is poured into a reaction kettle, preferably a polytetrafluoroethylene reaction kettle, sealed and placed in a blast oven, and heated to the target temperature for reaction.

[0041] In some embodiments of the present invention, preferably the temperature is 2 to 20 ° C min -1 , more preferably 2~15 °Cmin -1 The temperature is raised to 50-220°C at a rate of 100-220°C, and the reaction is kept at this temperature for 6-72 h, preferably at 100-120°C for 8-48 h.

[0042] According to the present invention, after the reaction is completed, the reactor is naturally cooled to 10-40° C. and slowly opened to obtain a reddish-brown precipitate.

[0043] The present invention preferably washes and dries the obtained reddish brown precipitate. The washing is preferably performed using an ethanol reagent. Specifically, the present invention performs suction filtration and washing of the reddish brown precipitate using ethanol, and repeats this process 1 to 5 times.

[0044] The drying can be carried out by means well known to those skilled in the art. In some embodiments of the present invention, the drying is preferably vacuum drying, the drying temperature is 40 to 100° C., preferably 60 to 80° C., and the drying time is 6 to 48 hours, preferably 6 to 24 hours.

[0045] It can be seen that the preparation method of the above-mentioned two-dimensional amorphous copper-based MOF material provided by the present invention can directly synthesize the two-dimensional amorphous MOF material in one step without the need for secondary treatment. Compared with the currently commonly used preparation methods of inducing crystal collapse such as fluid static pressure, heating, mechanical stress, radiation and discharge, the steps are simpler, easier to implement, and more efficient, which is conducive to promoting large-scale production.

[0046] The present invention also provides a two-dimensional amorphous copper-based MOF material prepared according to the above preparation method. According to SEM characterization and TEM characterization, the two-dimensional amorphous copper-based MOF material is a two-dimensional nanosheet structure.

[0047] The present invention also provides an application of the two-dimensional amorphous copper-based MOF material in electrocatalytic CO2 reduction.

[0048] Specifically, in some embodiments of the present invention, the two-dimensional amorphous copper-based MOF material is dissolved in isopropanol, and 1~7 μL / mg (wherein mg refers to the mass of the two-dimensional amorphous copper-based MOF material) of the binder is added, and the final solution concentration is 2~17 mg / mL (referring to the concentration of the two-dimensional amorphous copper-based MOF material in isopropanol); the binder includes any one or more of Nafion solution, sodium alginate, polytetrafluoroethylene micropowder or polyvinylidene fluoride. Then the solution is uniformly coated on the surface of the gas diffusion electrode, and the coating includes one of drip coating, spray coating, scraping coating, and spin coating; then dried at 50~90°C for 1~8 h to obtain a two-dimensional amorphous Cu-based MOF catalyst. The present invention has no particular restrictions on the gas diffusion electrode, which is well known to those skilled in the art and can be a general commercial product.

[0049] Furthermore, in the electrocatalytic CO2 reduction system, the above-mentioned two-dimensional amorphous Cu-based MOF catalyst was used as the working electrode, the nickel foam was used as the counter electrode, and the Ag / AgCl electrode was used as the reference electrode to form a three-electrode system. The electrocatalytic CO2 reduction was carried out in a flow cell in a constant voltage mode to obtain ethylene, ethanol, C 2+ The electrolyte is selected from potassium hydroxide, potassium bicarbonate, sodium bicarbonate, and potassium sulfate; the voltage range of the above constant voltage mode is -0.5~-2 vs. RHE.

[0050] The test showed that the non-periodic structure of the two-dimensional amorphous Cu-based MOF catalyst has excellent catalytic activity. In particular, the catalyst can effectively increase the production of C, including ethylene, ethanol and acetic acid. 2+ The selectivity of the product, C 2+ The Faradaic efficiency of the product is as high as 68.7%.

[0051] In order to further illustrate the present invention, the following examples are provided for detailed description. The experimental raw materials used in the following examples of the present invention are all common commercially available products.

[0052] Example 1

[0053] A one-step method for preparing a two-dimensional amorphous Cu-based MOF material comprises the following steps:

[0054] (1) Weigh 16 mL of N,N-dimethylformamide and acetonitrile respectively, mix them thoroughly, and obtain a mixed solution with a total volume of 32 mL. Divide it into two solutions by volume; weigh 125.5 mg of Cu(NO3)2•3H2O and 144 mg of DHTA (the molar ratio of Cu to the organic ligand DHTA is 1:1.4) respectively and dissolve them in the two mixed solutions. Stir at 600 rpm for 20 min to fully dissolve them. Record them as solution A (i.e., Cu(NO3)2•3H2O solution) and solution B (i.e., DHTA solution). Keep the stirring speed of solution A unchanged, slowly pour solution B into solution A to fully mix the two solutions; keep the original speed unchanged, and repeatedly measure the pH value of the solution. When the pH value of the solution stabilizes at 2.4 and the positive and negative errors are ≤0.2, it proves that the reaction solution has stabilized and is ready for use;

[0055] (2) Pour the reaction solution into a 45 mL polytetrafluoroethylene reactor, seal it and place it in a forced air oven. Set the heating rate to 8 °C min -1 , the reaction temperature is 120°C, and the reaction time is 24 h;

[0056] (3) After the reaction is completed, the reactor is cooled naturally to 30°C. Install a suction filtration device, add a small amount of ethanol to the filter paper, slowly turn on the vacuum pump, remove some of the air in the suction filtration bottle, and make the filter paper close to the bottom of the funnel. Pour the reacted solution into the suction filtration bottle and start suction filtration; add an appropriate amount of ethanol to the funnel, wash the precipitate on the filter paper, let it stand for 3 minutes, and then drain it; repeat the washing process 3 times to wash away the impurities remaining on the precipitate. Finally, vacuum dry at 80°C for 12 hours to obtain a two-dimensional amorphous Cu-MOF material.

[0057] Example 2

[0058] A one-step method for preparing a two-dimensional amorphous Cu-based MOF material comprises the following steps:

[0059] (1) Weigh 19.2 mL of N,N-dimethylformamide and 12.8 mL of acetonitrile respectively, mix them thoroughly to form a mixed solution with a total volume of 32 mL, and divide it into two solutions by volume; weigh 82.49 mg of CuSO4•5H2O and 144 mg of DHTA (the molar ratio of Cu to the organic ligand DHTA is 1:2.2) respectively and dissolve them in the two mixed solutions, stir at 800 rpm for 60 min to fully dissolve them, and record them as solution A and solution B. Keep the stirring speed of solution A unchanged, slowly pour solution B into solution A to fully mix the two solutions; keep the original speed unchanged, repeatedly measure the pH value of the solution, when the pH value of the solution is stable at 3.2, and the positive and negative errors are ≤0.2, it proves that the reaction solution has stabilized and is ready for use;

[0060] (2) Pour the reaction solution into a 45 mL polytetrafluoroethylene reactor, seal it and place it in a forced air oven. Set the heating rate to 8 °C min -1 , the reaction temperature is 80°C and the reaction time is 48 h;

[0061] (3) After the reaction is completed, the reactor is cooled naturally to 30°C. Install a suction filtration device, add a small amount of ethanol to the filter paper, slowly turn on the vacuum pump, remove some of the air in the suction filtration bottle, and make the filter paper close to the bottom of the funnel. Pour the reacted solution into the suction filtration bottle and start suction filtration; add an appropriate amount of ethanol to the funnel, wash the precipitate on the filter paper, let it stand for 3 minutes, and then drain it; repeat the washing process 3 times to wash away the impurities remaining on the precipitate. Finally, vacuum dry at 80°C for 12 hours to obtain a two-dimensional amorphous Cu-MOF material.

[0062] Example 3

[0063] A one-step method for preparing a two-dimensional amorphous Cu-based MOF material comprises the following steps:

[0064] (1) Weigh 8 mL of N,N-dimethylformamide and 24 mL of acetonitrile respectively, mix them thoroughly to form a mixed solution with a total volume of 32 mL, and divide it into two solutions by volume; weigh 206.53 mg of CuCl2•2H2O and 144 mg of DHTA (the molar ratio of Cu to the organic ligand DHTA is 1:0.6) respectively and dissolve them in the two mixed solutions, stir at 600 rpm for 60 min to fully dissolve them, and record them as solution A and solution B. Keep the stirring speed of solution A unchanged, slowly pour solution B into solution A to fully mix the two solutions; keep the original speed unchanged, repeatedly measure the pH value of the solution, when the pH value of the solution stabilizes at 2.67, and the positive and negative errors are ≤0.2, it proves that the reaction solution has stabilized and is ready for use;

[0065] (2) Pour the reaction solution into a 45 mL polytetrafluoroethylene reactor, seal it and place it in a forced air oven. Set the heating rate to 10 °C min -1 , the reaction temperature was 100°C and the reaction time was 36 h;

[0066] (3) After the reaction is completed, the reactor is cooled naturally to 30°C. Install a filtration device, add a small amount of ethanol to the filter paper, slowly open the vacuum pump, remove some of the air in the filtration bottle, and make the filter paper close to the bottom of the funnel. Pour the solution after the reaction into the filtration bottle and start filtration; add an appropriate amount of ethanol to the funnel, wash the precipitate on the filter paper, let it stand for 6 minutes, and then drain it; repeat the washing process 3 times to wash away the impurities remaining on the precipitate. Finally, vacuum dry at 80°C for 24 hours to obtain a two-dimensional amorphous Cu-MOF material.

[0067] Example 4

[0068] A one-step method for preparing a two-dimensional amorphous Cu-based MOF material comprises the following steps:

[0069] (1) Weigh 16 mL of N,N-dimethylformamide and 16 mL of acetonitrile respectively, mix them thoroughly to form a mixed solution with a total volume of 32 mL, and divide it into two solutions by volume; weigh 129.62 mg of CuSO4•5H2O and 144 mg of 2,3-dihydroxyterephthalic acid (the molar ratio of Cu to organic ligand is 1:1.4) respectively and dissolve them in the two mixed solutions, stir at 800 rpm for 60 min to fully dissolve them, and record them as solution A and solution B. Keep the stirring speed of solution A unchanged, slowly pour solution B into solution A to mix the two solutions thoroughly; keep the original speed unchanged, repeatedly measure the pH value of the solution, when the pH value of the solution is stable at 2.4, and the positive and negative errors are ≤0.2, it proves that the reaction solution has stabilized and is ready for use;

[0070] (2) Pour the reaction solution into a 45 mL polytetrafluoroethylene reactor, seal it and place it in a forced air oven. Set the heating rate to 8 °C min -1 , the reaction temperature is 120°C, and the reaction time is 48 h;

[0071] (3) After the reaction is completed, the reactor is cooled naturally to 30°C. Install a suction filtration device, add a small amount of ethanol to the filter paper, slowly turn on the vacuum pump, remove some of the air in the suction filtration bottle, and make the filter paper close to the bottom of the funnel. Pour the reacted solution into the suction filtration bottle and start suction filtration; add an appropriate amount of ethanol to the funnel, wash the precipitate on the filter paper, let it stand for 3 minutes, and then drain it; repeat the washing process 3 times to wash away the impurities remaining on the precipitate. Finally, vacuum dry at 80°C for 12 hours to obtain a two-dimensional amorphous Cu-MOF material.

[0072] Comparative Example 1

[0073] This comparative example provides a Cu-based MOF material, comprising the following steps:

[0074] Dissolve 125.5 mg of Cu(NO3)2•3H2O and 144 mg of DHTA in 32 mL of N,N-dimethylformamide and stir at 800 rpm for 20 min to fully dissolve. Pour the reaction solution into a 45 mL polytetrafluoroethylene reactor, seal it and place it in a forced air oven. Set the heating rate to 8 °C min -1 , the reaction temperature is 120°C, and the reaction time is 24 h. After the reaction is completed, the reactor is allowed to cool naturally to 30°C. Install a suction filtration device, add a small amount of ethanol to the filter paper, slowly turn on the vacuum pump, remove some of the air in the suction filtration bottle, and make the filter paper close to the bottom of the funnel. Pour the reacted solution into the suction filtration bottle and start suction filtration; add an appropriate amount of ethanol to the funnel, wash the precipitate on the filter paper, let it stand for 3 min, and then drain it; repeat the washing process 3 times to wash away the impurities remaining on the precipitate. Finally, vacuum dry at 80°C for 12 h to obtain a two-phase mixture containing crystalline Cu (such as Figure 1 Curve b in .

[0075] Comparative Example 2

[0076] This comparative example provides a Cu-based MOF material (with 2-aminoterephthalic acid as an organic ligand), comprising the following steps:

[0077] Dissolve 125.5 mg of Cu(NO3)2•3H2O and 144 mg of 2-aminoterephthalic acid in a mixed solution containing 16 mL of N,N-dimethylformamide and 16 mL of acetonitrile, and stir at 600 rpm for 20 min to fully dissolve. Pour the reaction solution into a polytetrafluoroethylene reactor with an inner volume of 45 mL, seal it, and place it in a forced air oven. Set the heating rate to 8 °C min -1, the reaction temperature was 120°C, and the reaction time was 24 h. After the reaction was completed, the reactor was cooled naturally to 30°C. The precipitate obtained after the reaction was filtered and washed with ethanol. After washing three times, it was vacuum dried at 80°C for 12 h to obtain a crystalline Cu-based MOF material (such as Figure 1 Curve c in ).

[0078] In the present invention, the two-dimensional amorphous Cu-MOF materials prepared in the above-mentioned embodiments 1 to 4 have similar structures and properties. The following only takes embodiment 1 as an example to characterize and test the properties of the prepared two-dimensional amorphous Cu-MOF material.

[0079] XRD test was performed on the two-dimensional amorphous Cu-MOF material obtained in Example 1 and the Cu-based MOF material obtained in Comparative Examples 1 and 2. The results are as follows: Figure 1 As shown. Among them, Figure 1 Curve a in FIG. 1 is the XRD pattern of the two-dimensional amorphous Cu-MOF material obtained in Example 1. Figure 1 Curve b in FIG. 1 is the XRD pattern of the Cu-based MOF material obtained in Comparative Example 1. Figure 1 Curve c in FIG. 1 is the XRD pattern of the Cu-based MOF material obtained in Comparative Example 2. Figure 1 It can be seen from curve a in the figure that there is no diffraction peak, which proves that the material has an amorphous structure. Figure 1 The curve a in Figure 1 By comparing curves b and c in the figure, it can be seen that when there is no acetonitrile in the organic solvent, or when other organic ligands are used, the crystal structure of the Cu-MOF material will be affected.

[0080] The two-dimensional amorphous Cu-MOF material obtained in Example 1 was characterized by SEM and TEM. Figure 2~3 shown.

[0081] By SEM ( Figure 2 ) and TEM ( Figure 3 ) It can be observed that the prepared amorphous Cu-MOF material is a two-dimensional nanosheet.

[0082] Evaluation of electrocatalytic CO2 reduction performance:

[0083] The electrode prepared with the two-dimensional amorphous Cu-MOF material obtained in Example 1 as the catalyst was used as the working electrode, the nickel foam was used as the counter electrode, and the Ag / AgCl electrode was used as the reference electrode to form a three-electrode system. 1 M KOH alkaline solution was used as the electrolyte, and the electrocatalytic CO2 reduction was carried out in a constant voltage mode in a flow cell. The applied potential range was -0.5~-2 vs. RHE, specifically -0.55 V, -0.75 V, -0.95 V, -1.15 V, -1.35 V, -1.55 V, -1.75 V, -1.95 V. After a period of electrolysis, the reacted gas was collected with a closed air bag. The gas phase product was detected using a gas chromatograph, and the liquid phase product was detected using a liquid nuclear magnetic resonance spectrometer.

[0084] Figure 4 This is the Faraday efficiency diagram of various products obtained by electrocatalytic CO2 reduction of two-dimensional amorphous Cu-MOF materials in Example 1. Through analysis, it can be seen that when the electrocatalytic CO2 reduction test is carried out in the potential range of -0.55~-1.95 V vs. RHE, the products obtained are ethylene, ethanol, acetic acid, carbon monoxide, hydrogen, formic acid and methane, among which C 2+ The Faraday efficiency of the product can reach 68.7%. Compared with Example 1, under the same conditions, the products of Comparative Examples 1 and 2 during the electrocatalytic reduction of CO2 are mainly C1 products such as carbon monoxide, formic acid, and methane. 2+ The product content is low, which shows that the performance of the materials obtained in Comparative Examples 1-2 as working electrodes is worse than that of the two-dimensional amorphous Cu-MOF material provided in the embodiment.

[0085] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a two-dimensional amorphous copper-based MOF material, characterized in that: The following steps are involved: A mixed solution of organic ligand, copper salt and organic solvent is reacted in a closed environment to obtain a two-dimensional amorphous copper-based MOF material; The organic ligand is selected from any one or more of 2-hydroxyterephthalic acid, 2,3-dihydroxybenzoic acid, 2,3-dihydroxyterephthalic acid, 2,5-dihydroxyterephthalic acid, 2,5-dihydroxybenzoic acid, 2,6-dihydroxybenzoic acid, 4-hydroxybenzoic acid or p-hydroxybibenzoic acid; The organic solvent is a mixed solvent of N,N-dimethylformamide and acetonitrile, and the volume ratio of N,N-dimethylformamide to acetonitrile is 5:1-1:

11.

2. The preparation method according to claim 1, characterized in that: The copper salt is selected from any one or more of Cu(NO3)2, Cu(NO3)2•3H2O, CuSO4, CuSO4•5H2O, CuCl2, CuCl2•2H2O, CuCrO4•2H2O or CuCr2O7•2H2O; The molar ratio of copper in the copper salt to the organic ligand is 4:1 to 1:

13.

3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of copper in the copper salt to the organic ligand is 4:1 to 1:

8.

4. The preparation method according to any one of claims 1 to 3, characterized in that The volume ratio of the N,N-dimethylformamide to acetonitrile is 3:1 to 1:

6.

5. The preparation method according to any one of claims 1 to 4, characterized in that The mixed solution of the organic ligand, copper salt and organic solvent is obtained by dissolving the organic ligand and copper salt in the organic solvent; The dissolving is carried out at a rotation speed of 50 to 1400 rpm; The pH value of the mixed solution is 1-6.

7.

6. The preparation method according to any one of claims 1 to 5, characterized in that The reaction was carried out at 2-20 °C min -1 The temperature is raised to 50~220℃ at a rate of The reaction is kept at 50-220°C for 6-72 hours.

7. The preparation method according to any one of claims 1 to 6, characterized in that The reaction further includes washing and drying steps.

8. A two-dimensional amorphous copper-based MOF material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The two-dimensional amorphous copper-based MOF material is a two-dimensional nanosheet structure.

9. Use of the two-dimensional amorphous copper-based MOF material prepared by the preparation method according to any one of claims 1 to 7 or the two-dimensional amorphous copper-based MOF material according to claim 8 in electrocatalytic CO2 reduction.

10. The use according to claim 9, characterized in that: In the electrocatalytic CO2 reduction, the working electrode comprises the two-dimensional amorphous copper-based MOF material prepared by the preparation method according to any one of claims 1 to 7 or the two-dimensional amorphous copper-based MOF material according to claim 8.

Citation Information

Patent Citations

  • Metal organic framework material CuBDC nano sheet, preparation method and application thereof

    CN106252663A

  • Two-dimensional CuBDC nanosheet and preparation method thereof

    CN117757089A

  • Method for constructing amorphous mixed matrix membrane based on low-temperature induction

    CN118286892A